Effect of the flavonoids quercetin and taxifolin on UVA-induced damage to human primary skin keratinocytes and fibroblasts - Rajnochová Svobodová, Alena; Ryšavá, Alena; Čížková, Kateřina; Roubalová, Lenka; Ulrichová, Jitka; Vrba, Jiří; Zálešák, Bohumil; Vostálová, Jitka (Photochemical & photobiological sciences, 2022)
The ultraviolet (UV) part of solar radiation can permanently affect skin tissue. UVA photons represent the most abundant UV component and stimulate the formation of intracellular reactive oxygen species (ROS), leading to oxidative damage to various biomolecules. Several plant-derived polyphenols are known as effective photoprotective agents. This study evaluated the potential of quercetin (QE) and its structurally related flavonoid taxifolin (TA) to reduce UVA-caused damage to human primary dermal fibroblasts (NHDF) and epidermal keratinocytes (NHEK) obtained from identical donors. Cells pre-treated with QE or TA (1 h) were then exposed to UVA light using a solar simulator. Both flavonoids effectively prevented oxidative damage, such as ROS generation, glutathione depletion, single-strand breaks formation and caspase-3 activation in NHDF. These protective effects were accompanied by stimulation of Nrf2 nuclear translocation, found in non-irradiated and irradiated NHDF and NHEK, and expression of antioxidant proteins, such as heme oxygenase-1, NAD(P)H:quinone oxidoreductase 1 and catalase. For most parameters, QE was more potent than TA. On the other hand, TA demonstrated protection within the whole concentration range, while QE lost its protective ability at the highest concentration tested (75 μM), suggesting its pro-oxidative potential. In summary, QE and TA demonstrated UVA-protective properties in NHEK and NHDF obtained from identical donors. However, due to the in vitro phototoxic potential of QE, published elsewhere and discussed herein, further studies are needed to evaluate QE safety in dermatological application for humans as well as to confirm our results on human skin ex vivo and in clinical trials.
Keywords: oxidační stres; Flavonoids; Oxidative Stress; fibroblasty; Ultraviolet Rays; Fibroblasts; quercetin; keratinocyty; Keratinocytes; kůže; flavonoidy; ultrafialové záření; Humans; lidé; Quercetin; Skin